PENGARUH KUALITAS PRODUK, HARGA, DAN KELOMPOK ACUAN TERHADAP KEPUTUSAN PEMBELIAN PELUMAS MOTOR ENDURO 4T RACING PERTAMINA DI KOTA PONTIANAK - B31112114, Handoko S (Jurnal Manajemen Update, 2016)
This study aimed to analyze the effect of product quality, price and the reference group on product purchasing decisions lubricants Pertamina  Enduro4T  Racing motorcycle in Pontianak. This study uses quantitative methods of causal form. The population in this study is that people of Pontianak who use a  lubricants motorcycle  Enduro 4T Racing Pertamina. The sampling technique used in this research is non probability sampling, then selected as many as 100 respondents. Analysis technique used is multiple linear regression analysis using SPSS versi16.0. The Results of the analysis of the data obtained showed that the reference group did not significantly influence the purchasing decision Enduro4T Racing Pertamina lubricants. While the quality of the product and the price significantly influence purchasing decisions Enduro 4T Racing Pertamina motorcycle lubricants in the community of Pontianak, with a significance value of 0.000 and 0.009, and R2 value of 33.6%, while the remaining 66.4% are other factors not examined in this research. Keywords: product quality, price, reference group, a purchase decision.